KONSEP IMPLEMENTASI TAHSIN TILAWAH DALAM PEMBELAJARAN MAKHARIJUL HURUF KELAS 2 PUTRI DIPONDOK PESANTREN BEQURANIC BENGKALIS - Melisa, Sri; Robi’ah, Robi’ah (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
This research concentrates on improving the ability to read the Qur’an of students at the Bequranic Islamic Boarding School in Bengkalis through the tahsin tilawah method in learning makharijul letters, while this research is descriptive qualitative research and uses the type of field research or field research. Data sources in this study used Islamic education literature and scientific journals. Some research findings that can be described, that there are still some students who have difficulty following learning because of difficulties in pronouncing hijaiyah letters and there are still students who are not disciplined in following learning. However, on the other hand, students become more active in learning because of the motivation and desire to continue to improve the reading of the Qur’an as a form of obedience to Allah SWT